Optimization of Philippine National Railways operations based on capacity and headway - Enghoy, John Carl Vincent L.; Manguera, Manicar V.; Sigua, Ricardo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The Philippine National Railways (PNR) is one of the old state-owned railway companies located in Luzon. These past few years, PNR Metro Commuter Line experiences problems on congestion because the passenger volume demand exceeds its train capacity. The Metro Commuter Line can only serve a maximum of 47,000 passengers daily but at least 70,000 passengers ride here daily. This study aims to optimize the PNR operations by recommending an optimum combination of capacity and headway to meet its passenger volume demand. The actual line demand, capacity and minimum headway were determined through coach occupancy and demand surveys. Another survey was done in order to determine the number of unserved passengers or people who were not able to board the train after they arrive at a certain station. Based on the analyses, the researchers suggested head ways and number of trains required for different conditions: the current condition, tolerable crush loading, and condition that take into account the comfort of the passengers. For the current condition, the required headway is 24 minutes and 6 trains are needed. For the tolerable crush loading condition, the required headway is 20 minutes and 7 trains are needed. For the comfort of passengers, the required headway is 13 minutes and 11 trains are needed. In order to lessen the unserved passengers, at least 22-minute headway is required.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Railroads -- Passenger traffic; Railroads -- Management. -- Philippines